2B or not 2B? Disparate discrimination of functional VWF discordance using different assay panels or methodologies may lead to success or failure in the early identification of type 2B VWD - Favaloro, Emmanuel J.; Bonar, Roslyn; Meiring, Muriel; Street, Alison; Marsden, Katherine; the RCPA QAP in Haematology; on behalf of (Thrombosis and Haemostasis, 2007)
Laboratory proficiency in the identification of functional von Willebrand factor (VWF) discordance in type 2B von Willebrand disease (VWD) was assessed by external quality assurance surveys conducted by the RCPA Haematology QAP, and using six different type 2B VWD plasma samples (three historical and three previously unpublished) tested by up to 52 laboratories. For the three most recent samples, functional VWF discordance was either not identified in testing or by interpretation with misidentification as ‘normal’ or ‘type 1 VWD’, on average for 25.7% of test occasions when laboratories performed VWF:Ag and VWF:RCo as their primary VWF test panel, but somewhat fewer occasions (10.9%) for laboratories that incorporated VWF:CB as an additional functional VWF assay. VWF assay sub-methodologies also influenced the appropriate identification of samples as potentially type 2 VWD, and VWF functional discordance was more consistently identified when laboratories used (i) automated platelet agglutination for VWF:RCo compared to classical platelet aggregometry, (ii) inhouse VWF:CB assays compared to commercial kit methods, and (iii) automated LIA-based ‘VWF:Activity’ assays compared to ELISA based assays.We conclude that:(i) laboratories are generally proficient in tests for VWD but interpretative diagnostic errors do occur; (ii) correct diagnosis is more likely when test panels are more comprehensive and include the VWF:CB; (iii) sub-methodology influences the appropriate identification of VWF functional discordance. On the basis of these findings, we provide a series of recommendations to enable the appropriate laboratory identification of VWD, in particular type 2B VWD.
Keywords: von Willebrand factor; VWF; von Willebrand’s disorder; von Willebrand’s disease; VWD; laboratory assessment; survey; haemostasis testing; diagnostic practice; quality control; quality assurance